An Studi Kepuasan Pengguna Layanan Farmasi di Klinik Kesehatan X di Jember - Isnawati, Nafisah; Nuraini , April; Sholeh, Ayu Angger Putri M.; Cendekiawan, Khrisna Agung; Khairomatul L , Atmanita (Journal of Pharmaceutical and Sciences, 2025)
User satisfaction with pharmaceutical services in healthcare facilities is a critical indicator of service quality and plays an essential role in improving the overall healthcare experience. High satisfaction levels reflect the appropriateness, efficiency, and responsiveness of pharmacy services. This study aimed to evaluate the level of satisfaction among users of pharmaceutical services at the Pharmacy Installation of Clinic X in Jember. This study employed a prospective observational design conducted in August 2025. The study population consisted of outpatients receiving pharmaceutical services, and the sample included patients who met the inclusion criteria and agreed to participate. A total of 160 respondents were selected using consecutive sampling, a non-probability sampling technique. Data were collected using a structured questionnaire and tables documenting respondent characteristics and patient satisfaction outcomes. Satisfaction was assessed across five dimensions of pharmaceutical service quality: reliability, responsiveness, empathy, tangibles, and assurance. Descriptive analysis was used to summarize respondent characteristics and satisfaction scores. Of the 160 respondents, the majority were female (71.25%) and within the age group of 25–44 years (53.75%). Most respondents had a senior high school education or equivalent (50.00%), were self-employed (64.38%), and had visited the clinic twice (38.75%). Satisfaction scores across service dimensions were as follows: reliability 97.1%, responsiveness 65.5%, empathy 68.1%, tangibles 82.1%, and assurance 66.7%. The overall Customer Satisfaction Index (IKM) was 82.2%, categorizing the service quality as good. The results indicate that users were generally satisfied with the pharmaceutical services provided at Clinic X. The high score in the reliability dimension suggests consistent service performance and accuracy. However, the lower scores in responsiveness, assurance, and empathy highlight areas requiring improvement, particularly regarding timely service delivery, confidence-inspiring interactions, and patient-centered communication. Although the overall satisfaction level was good, targeted improvements in these dimensions are essential for enhancing the overall quality of pharmaceutical care. Overall, the level of user satisfaction with pharmaceutical services at Clinic X was categorized as good, with an IKM score of 82.2%. All five dimensions of service quality were rated positively, although responsiveness, assurance, and empathy showed room for improvement. These results highlight the importance of strengthening service quality components beyond technical accuracy to ensure a more holistic and patient-centered pharmaceutical care experience.